2005
DOI: 10.1590/s0103-50532005000300009
|View full text |Cite
|
Sign up to set email alerts
|

Electronic effects on the reactivity of cross-conjugated carbonyl systems with Fe2(CO)9

Abstract: Neste trabalho foram estudados os efeitos eletrônicos induzidos por p-substituintes no anel fenilico de diversos compostos carbonílicos conjugados [4-p-R-fenil-1-(1,3-ditiolano-2-ilideno)-3E-buteno-2-ona, onde R=NO 2 , Cl, Br, OMe, NEt 2 (2-6)], e sua reatividade frente a Fe 2 (CO) 9 usando o diagrama de Hammett. A estrutura dos compostos (3 e 4b) foi totalmente estabelecida por análise de difração de raio-X.The electronic effects induced by p-substituents on the phenyl ring of several novel crossconjugated ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Representative complexes 2g and 2l are illustrated in Figures and . The chalcone ligands exhibit the expected s-cis (single-bond geometry connecting the enone) conformation, and the bond lengths within the C−C−C−O framework exhibit the changes that are predicted on the basis of the bonding models described above; namely, the O 1 −C A and C B −C C bonds show significant lengthening on coordination to the metal, whereas C A −C B exhibits shortening, compared to the free ligand. , An examination of the bond angles around the iron indicates that the complexes are best considered to be six-coordinate octahedral species with three coordination sites occupied by the carbonyl ligands, with the remaining position occupied by O 1 , C C , and the center of the C A −C B bond. The mean bond angles around the iron for all six complexes are shown in Figure .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Representative complexes 2g and 2l are illustrated in Figures and . The chalcone ligands exhibit the expected s-cis (single-bond geometry connecting the enone) conformation, and the bond lengths within the C−C−C−O framework exhibit the changes that are predicted on the basis of the bonding models described above; namely, the O 1 −C A and C B −C C bonds show significant lengthening on coordination to the metal, whereas C A −C B exhibits shortening, compared to the free ligand. , An examination of the bond angles around the iron indicates that the complexes are best considered to be six-coordinate octahedral species with three coordination sites occupied by the carbonyl ligands, with the remaining position occupied by O 1 , C C , and the center of the C A −C B bond. The mean bond angles around the iron for all six complexes are shown in Figure .…”
Section: Resultsmentioning
confidence: 95%
“…Considerable substituent effects are also observed in the NMR spectra of the complexes and ligands; indeed, in the free ligand a linear correlation has been observed between the resonance for C C and the electronic properties of suitable substituents …”
Section: Resultsmentioning
confidence: 96%
“…Complex 5a was obtained in a trace amount. This compound has been obtained by other methods 13 and as subproduct of α,β-unsaturated ketone analogues in reactions brought about under similar conditions. , The novel complexes 5b and 5c are the principal products, and they arise from the C−S bond activation of 5 . This activation is not selective, as compared with complexes 2 and 3 .…”
Section: Resultsmentioning
confidence: 88%
“…Thus, when α,β-unsaturated ligands with a dithiol group react with diiron nonacarbonyl, they generate dinuclear complexes 1 . However, ligands that contain an additional conjugated double bond, such as 4-phenyl-1-(1,3-dithiolane-2-ylidene)-3 E -butenone, produce dinuclear Fe(0) complex 2 displaying C−S bond activation . We previously reported that this activation depends on the electronic density of the heterodienic moiety 3b.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation